BIOGRAFI H. MUHAMMAD (TOKOH SENIMAN HADRAH KOTA PONTIANAK) - Putra, Yoga Kharisma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This essay motivated by learning experience and interesting life from H. Muhammad life, from his art life, social life, and even his religion life. To discover that phenomenon, the writerÂ make a research problem, there are: how the biography of H. Muhammad and how H. Muhammad life in the art world to be a Hadrah artist in Pontianak City.The Method in this essay is descriptive method. The result of this research discover the biography of H. Muhammad from his birth in 1914 to the day that he dies in 6th September 1981. His first contribution is to existence Hadrah in Pontianak City until today, with made a Hadrah Group and recruit Hadrah student.The second contribution for Hadrah development in Pontianak City, with create Hadrah lyrics based on the biography of Prophet Muhammad SAW in Indonesian. The third contribution on the Hadrah lyricsÂ based on the biography of Prophet Muhammad SAW in Indonesian created by H. Muhammad for the benefit of Melayu people, Islam people, and Hadrah artist in Pontianak City. Keywords : Biography, H. Muhammad ( a Hadrah artist figure in Pontianak City)